The structure of scientific revolutions - Kuhn, Thomas S. (Chicago The University of Chicago Press, 1996)
Thomas S. Kuhn's classic book is now available with a new index."A landmark in intellectual history which has attracted attention far beyond its own immediate field. . . . It is written with a combination of depth and clarity that make it an almost unbroken series of aphorisms. . . . Kuhn does not permit truth to be a criterion of scientific theories, he would presumably not claim his own theory to be true. But if causing a revolution is the hallmark of a superior paradigm, [this book] has been a resounding success." --Nicholas Wade, Science"Perhaps the best explanation of [the] process of discovery." --William Erwin Thompson, New York Times Book Review"Occasionally there emerges a book which has an influence far beyond its originally intended audience. . . . Thomas Kuhn's The Structure of Scientific Revolutions . . . has clearly emerged as just such a work." --Ron Johnston, Times Higher Education Supplement"Among the most influential academic books in this century." --Choice--One of "The Hundred Most Influential Books Since the Second World War," Times Literary SupplementThomas S. Kuhn was the Laurence Rockefeller Professor Emeritus of linguistics and philosophy at the Massachusetts Institute of Technology. His books include The Essential Tension; Black-Body Theory and the Quantum Discontinuity, 1894-1912; and The Copernican Revolution.The Structure of Scientific Revolutions by Thomas Kuhn, is an analysis of the history of science, published in 1962. Its publication was a landmark event in the history, philosophy, and sociology of scientific knowledge and it triggered an ongoing worldwide assessment and reaction in and beyond those scholarly communities. In this work, Kuhn challenged the then prevailing view of progress in "normal science." Scientific progress had been seen primarily as "development-by-accumulation" of accepted facts and theories. Kuhn argued for an episodic model in which periods of such conceptual continuity in normal science were interrupted by periods of revolutionary science. During revolutions in science the discovery of anomalies leads to a whole new paradigm that changes the rules of the game and the "map" directing new research, asks new questions of old data, and moves beyond the puzzle-solving of normal science.[1]For example, Kuhn's analysis of the Copernican Revolution emphasized that, in its beginning, it did not offer more accurate predictions of celestial events, such as planetary positions, than the Ptolemaic system, but instead appealed to some practitioners based on a promise of better, simpler, solutions that might be developed at some point in the future. Kuhn called the core concepts of an ascendant revolution its "paradigms" and thereby launched this word into widespread analogical use in the second half of the 20th century. Kuhn's insistence that a paradigm shift was a mélange of sociology, enthusiasm and scientific promise, but not a logically determinate procedure, caused an uproar in reaction to his work. Kuhn addressed concerns in the 1969 postscript to the second edition. For some commentators it introduced a realistic humanism into the core of science while for others the nobility of science was tarnished by Kuhn's introduction of an irrational element into the heart of its greatest achievements.